Studies On Embryonic Development In Thoroughbred Mares - Arbal, R. W.; Ingawale, M.V.; Deshmukh, S.G.; Hajare , S.W. (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
This study was planned to determine the embryonic developments in 12 Thoroughbred mares. The follicular growths were recorded in mares from day 8 postpartum till ovulation daily by using ultrasound machine with 7.5 MHz transrectal probe. All mares which were detected with largest follicle size and a characteristic uterine pattern of edema (cart-wheel like appearance) were mated with stallion every second day. Ultrasonography was carried out daily from day 14th post-mating till day 40 (ovulation = day 0) for detection of early of pregnancy and to monitor the conceptus. Embryonic vesicle was observed for the first time on day 14 in all mares with mean size of 10.25±0.59 mm. The fixation of vesicle, loss of spherical shape of vesicle, detection of embryo, detection of heart beats, detection of allantoic sac and start of fetal ascent were observed on 16.75±1.52, 20.66±1.86, 25.08±2.23, 28.16±2.45, 27.83±2.43 and 27.83±2.43 days post-mating, respectively. It was concluded that ultrasonic detection of early pregnancy and embryonic developments studies is an accurate tool and simple way for estimating the age of pregnancy in Thoroughbred mares.